Peningkatan Keaktifan Dan Hasil Belajar Ekonomi Melalui Permainan Menempel Rupiah - Eni Suciati (PGSD Universitas Muria Kudus, 2023)
The purposes of this study were (1) to examine the increase in the activity of class XII MIPA 6 SMA Negeri 1 Rembang in learning accounting economics by applying the rupiah stick game, and (2) to examine the increase in student learning outcomes in class XII MIPA 6 SMA Negeri 1 Rembang in learning accounting economics with the application of the rupiah sticking game.This Classroom Action Research was conducted in two cycles, each cycle consisting of two meetings. The research subjects were students of class XII MIPA 6 SMA Negeri 1 Rembang with a total of 35 students consisting of 9 male students and 26 female students. The data collection method used is the observation method to determine student activity and the test method to determine student learning outcomes. Data analysis techniques in this study were carried out quantitatively and qualitatively.The results showed an increase in student activity and learning outcomes. After the action was taken, the average level of activity increased from 55.41% in the less active category to 67.19% in the active category. The average pre-cycle learning result was 53, after cycle 1 it increased to 68 and after the implementation of the actions in cycle 2 it became 74. Student completeness in cycle 2 increased by 66% and has met the success indicators that have been set in this study. This proves that the Rupiah Sticking Game Media can be used to increase student activity and learning outcomes.